KESANTUNAN TINDAK TUTUR DIREKTIF DALAM PEMBELAJARAN BAHASA INDONESIA DI SMP NEGERI 2 SAMALANTAN - Setyaningsih, Eli; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe speech acts of a teacher in the learning process at school are one way of transferring knowledge to students. Besides, teachers should give students examples of how to speak politely, including learning Indonesian in the classroom, the directive politeness of speech is very important to highlight, thus became interesting to be the focus of research. This study aims to describe forms and contextual functions of the politeness of direct speech acts in the IndonesianÂ language subject for seventh-grade at SMPN 2 Samalantan. The method used in this study was descriptive in the form of qualitative research. Research data were collected from teacher and class VII B students of SMPN 2 Samalantan. The data were in the form of speech acts of directive conversation, collected using observation, recording, and field notes techniques. Based on the analysis, the politeness forms of speech acts from the speaker and interlocutor include asking, commanding, inviting/persuading, advising, criticizing, and prohibiting. The results showed that the form of politeness of directive speech acts dominantly uttered in the learning activities was commanding.Â Â Keywords: Contextual, Directive Speech Acts, Politeness